Manajemen Proyek Sistem Informasi Kesehatan Mental Mahasiswa berbasis Akun Tiktok @healing.campus - Rio Anugrah; Najla Puteri Salsabila; Nurul Agami; Faresh Utomo; Vitha Anggraini; Aryo Wiranata; M Arief Rahman (Sultan Publisher, 2024)
Project Management for Mental Health Information System among Students Based on TikTok Accounts (Healing.Campus) is an initiative aimed at providing an alternative solution to assist students in dealing with mental health issues. Mental health is a crucial aspect of general well-being, yet issues related to mental health among students remain constrained and limited. This research employs a qualitative research method and data analysis techniques as a theoretical study. Qualitative research methods are used due to literature indicating constraints and limitations in using TikTok as a platform for developing students' mental health. Data analysis techniques, as part of the theoretical study, are utilized to determine whether the hypotheses formulated in the literature review are accurate. The research findings demonstrate that the TikTok-based information system, Healing.Campus, for mental health has achieved satisfactory outcomes, reflecting a significant positive impact on its audience. The Healing.Campus TikTok account has been able to contribute positively to students' mental health. Motivational video content has successfully created a supportive and empathetic atmosphere, provided practical solutions, and reduced stigma associated with mental health issues. It has successfully attained positive and significant outcomes in aiding students in addressing mental health concerns. This TikTok account proves its effectiveness in creating a supportive and empathetic atmosphere, offering practical solutions, and reducing the stigma associated with mental health problems. The existence of this mental health information system is expected to provide motivation and encouragement to students facing difficulties.